Studi Komparasi Kesiapan Indonesia Menerapkan Carbon Trade 2025 - Ferdiansyah, Muhammad Rayhan Ali; Rosyadah, Hanif; Ramadhan, Fikri Fajar (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to assess Indonesia’s readiness to implement carbon trading in 2025 to achieve net zero emissions by 2060. The research uses a mixed-method approach, combining literature review, multivariate linear regression, and Vector Error Correction Model (VECM). The results indicate that the Human Development Index (HDI) has a negative and significant impact on CO2 emissions in the long term. This impact is greater than the results observed in Singapore and Thailand. With established policies and a demographic bonus in 2045, optimizing human resources is crucial for achieving net zero emissions by 2060.